Developing English interactive learning multimedia of listening and speaking for the tenth-grade students - An-Nur, Raizsa; Suryaman, Maman (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
This research aims to develop a computer-based interactive learning multimedia for the teaching of English Listening and Speaking for the tenth grade students in Pelabuhanratu. This study adapted the development model suggested by Sugiyono (2014), the steps are: (1) exploration (2) development of the prototype, (3) expert validation and revision, and (4) try-out and final revision. The findings indicate that the appropriate learning multimedia for the tenth grade students in Pelabuhanratu are the learning multimedia that: (1) gives students a lot of oral cycle practice, (2) generates low pressure learning, (3) promotes student-centred learning, (4) trains students to practice micro skills of listening and speaking and (5) provides Bahasa Indonesia translation in the learning instruction. This product is rated as